PENGARUH KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI KOMISI PEMILIHAN UMUM KOTA KENDARI - La Ode Ahmad Darmawan; Eka Suaib; Muhammad Basri (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
The purpose of this research is to empirically investigate and  analyze the organizational commitment and job satisfaction of the employee performance of the general election commission in Kendari City simultaneously and partially. This study uses a quantitative approach, the data in this study using a questionnaire. The population in this study was 36 people who were also the research sample. The data analysis used multiple linear regression analysis.The results of this study indicate that organizational commitment and job satisfaction simultaneously have a significant effect on improving employee performance. This means that changes in increased organizational commitment and job satisfaction are reflected in emotional attachment to the workplace organization (affective commitment) and satisfaction with promotion has a positive and significant contribution to employee performance improvement, which is reflected in aspects of contextual performance, task performance and work behavior. Organizational commitment has a significant effect on employee performance. These results prove that high organizational commitment has a significant contribution to improving employee performance. High job satisfaction has a significant contribution to improving employee performance. This means that changes in job satisfaction that are reflected through satisfaction with pay, promotions, supervision, benefits, operating conditions, colleagues, nature of work, and communication have a significant contribution to improving employee performance.